Compreendendo a educação para a inclusão digital: uma análise dos sentidos atribuidos pelos monitores das escolas de inclusão digital e cidadania da EMATER-RN - Liberato, Antonio Carlos Teixeira (2010)
According to the methodological presuppositions of the understanding interview (KAUFMAAN, 1996), the present work aims to understand the Digital Inclusion starting from the oral speeches of eight monitors of Digital Inclusion and Citizenship Schools of the Technical Assistance and Rural Extension Company EMATER, located in municipal districts that belong to six regions of the state of Rio Grande do Norte. It also had the intention to analyze it (the Digital Inclusion), while educational process and its relation with the citizenship. In its first part, an analysis of the discussions about digital inclusion was developed, and a reflection about the new technologies in current times, followed by a contextualization of the rural space and the methodological course of the study, when its guiding axis and the travelled roads were presented, where the object of study is built slowly and progressively through a theoretical elaboration that increases day by day, as of the technologies forged in the field of research and formation of the subject. The second part presents the study of the collected information, that is organized in three chapters denominated as follows: Conceptions of the local context; What does digital inclusion mean? and The monitor as an educator. The reports do evidence a peculiar dissatisfaction with the social reality where they are found, that contradicts the positive reflections and perspectives of the studied authors, once that, within the actual conjuncture, the rural space has acquired another meaning, no longer being seen as a far late place. By trying to define the digital inclusion, the monitors make an association with change, the access to knowledge, active participation in society and improvement of the life conditions. Here a mission sense stands out, related to the ideological precept, which has been managing its activities. Towards the monitor‟s relation within the classroom, the senses evidence how they are and how they have been developing their daily activities. Tensions, fears and insecurities are identified, but at the same time, a compromise. The final considerations implicate to the need of reorientations in the formative process of this professionals, detaching the importance of their activities while agents of inclusion and social transformation